Is S-1 a Potential Game Changer in Adjuvant Therapy of Pancreatic Cancer? - Chaulagain, Chakra P; Rothschild, Janice; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
There remains a lack of consensus on the optimal adjuvant therapy for pancreatic cancer. In general, chemoradiation is favored in the United States and gemcitabine based chemotherapy is favored in Europe. Both of these approaches have been shown by large prospective, randomized trials to improve disease free survivals and in some studies overall survival. We present the summary of three abstracts from the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting and discuss their potential impact on our clinical practice. Adjuvant oral chemotherapy with S-1 (Fukutomi et al., Abstract #4008) has now emerged as a promising alternative to the traditional gold standard of intravenous gemcitabine in a relatively large randomized phase III clinical trial. Another study by Yoshitomi et al. (Abstract #4056) examined the value of adjuvant chemotherapy with S-1 alone versus combination of S-1 and gemcitabine versus gemcitabine alone in a three arm phase II clinical trial (CAP-002 Study). In terms of biomarkers in pancreatic cancer, Neoptolemos et al. presented the impact of hENT1 tumor levels on the outcome of the patients with pancreatic cancer (Abstract #4006) who had received adjuvant chemotherapy with either 5-flurouracil or gemcitabine in the ESPAC trial. Image: Composition and mechanism of action of S-1.